Reconstruction of the Concept of Maslahat-Based Maqasid al-Shariah in Contemporary Islamic Economics Theoretical Paradigmatic: Systematic Literature Review - Zulkarnaen Zulkarnaen; Muhammad Yafiz (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This research aims to reconstruct the concept of maqasid al-syari'ah based on maslahah in the perspective of contemporary Islamic economics by systematically examining conceptual, methodological, and paradigmatic developments in the existing literature. The research uses a systematic literature review (SLR) approach by following the PRISMA 2020 reporting flow. The literature search process was carried out through the Scopus database using keywords related to maqasid al-syari'ah, maslahah, and Islamic economics, so that 23 articles that met the inclusion criteria were obtained for analysis. Data were analyzed using thematic analysis and narrative synthesis to group findings into conceptual-theoretical, methodological-paradigmatic, and conceptual development synthesis. The results of the study show that contemporary Islamic economic literature has adopted a substantive maslahah orientation, especially in the study of Islamic banking, cash waqf, and Islamic social finance, but still places maqasid al-shari'ah implicitly and sectorally. The use of maqasid as the main paradigm of analysis is still limited, with the dominance of positivistic and evaluative approaches. Through the synthesis of literature, this study confirms the potential of maqasid al-syari'ah based on maslahah to be developed as an integrative and coherent Islamic economic paradigm. This research contributes to the strengthening of the conceptual framework of Islamic economics by placing maqasid al-syari'ah as the foundation of economic values, methods, and practices.